Sistem Pendukung Keputusan Penentuan Pemberian Reward Terbaik Terhadap Customer Dengan Metode SMART - Fatia Seftira; Hardini Novianti (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
Online Shop Shaqueena is an independent business sector engaged in selling beauty masks and various types of skincare products. For the sake of smooth business, the Shaqueena Store maintains good relations with consumers. One of the things that is done to establish good relations with consumers is to provide rewards or awards to the best customers. Based on observations, the process of selecting and recommending the best customers at the Shaqueena store is still done manually and randomly without using the help of the system. This manual and random selection is ineffective because the selection process itself is time-consuming and results in a lack of accuracy on which customers will be rewarded. This study aims to implement the SMART method in the reward system for customers. In its application the system is built using web-based programming and the PHP programming language with MySQL as the storage database. The method used in this study is the SMART method. Where SMART has flexibility in weighting, so it is suitable to be applied to the selection of rewards where there is no assessment weight. The result of this research is a website-based decision support system.